(untitled) (American Journal of Environment and Climate, 2023)
The day-by-day increment in the concentration of greenhouse gases (GHGs) in the atmosphere is widely believed to be a main contributing factor for climate change. It affects widely on diverse sectors such as water resources, agriculture, forestry, human health, biodiversity, and snow cover and aquatic life. Nepal is experiencing the adverse impact of climate change; this includes such as a variability in temperature and precipitation, overbank flooding from snow-fed rivers, and variability in available river and stream water quantity. Climate in the Nepal Himalayas is changing faster than the global average. Moreover, the changes in the high-altitudes have been found more pronounced than in the low-altitudes. Since, there is no definite trend that could be found in the annual precipitation records, clear decreasing trends could be seen in annual number of rainy days during the study period of 1971-2000. The glaciers in the Nepal Himalayas are shrinking rapidly and there will be no glaciers left by 2180. An accelerated glacier melt will cause an increase in water availability at the beginning but ultimately a decrease in water availability after the glaciers disappear. This will widen the gap between water supply and demand. Changing climate may further exacerbate the water stress which already happening in Nepal due to the monsoon dominated climate. Climate change (CC) will also further increase the seasonal imbalance- too much of water during rainy season and too less of it during dry seasons. Rainwater harvesting technology has the potential to provide numerous benefits to communities and individuals, particularly in areas where water resources are scarce or unreliable. From the analysis and through our research work it is found that if we can simply install and construct rainwater harvesting technology in our individual household only. It nearly fulfills about 15-25% of our domestic water demand. As in urban and rural area of Nepal still nearly about 50% of water demand is fulfilled by groundwater source which increase to 60-70% in dry season. The projected physical impacts of climate change on water resources would have substantial socioeconomic impacts and consequences for Nepal. The hydropower potential and agricultural production would be seriously affected by global warming. A reduction in agricultural production would be experienced due to water security and have significant impact on the food security and livelihoods of the subsistence farmers, who make the majority of the Nepal’s population. As the urgent need for climate change mitigation remains crucial, putting all the necessary resources and institutions in place for future adaptation is indispensable. The Inter-governmental Panel on Climate Change (IPCC) has listed rainwater-harvesting as a key strategy for a planned adaptation in the water sector. The policy statements about rainwater harvesting-based climate change adaptation are currently not being effectively coordinated.